Standard setting and carrier differentiation at seaports - Christopher B. Clott; Bruce C. Hartman; Robert Cannizzaro (Journal of Shipping and Trade (JST), 2018)
The deployment of mega container ships with a capacity for 18,000 + TEU on major trade lanes is a recent trend within the ocean shipping industry. Larger ships pose multiple challenges to ports and hinterland connections as well as to the beneficial cargo owners. To achieve maximum utilization of their larger vessels, carriers have entered cooperative global alliances on predetermined routes, resulting in new discharge patterns at U.S. ports. These multi-partner networks involve several competing firms which voluntarily and interactively engage in service delivery. Container carriage is increasingly competitive, and requires continuing cost reductions. There is increasing evidence, however, that cargo shippers are less satisfied with the service their supply chains are receiving. Standardizing process performance through supply chain integration and removing inefficiency will be needed to stabilize the international shipping market, but the question remains how ocean carriers will be able differentiate themselves and create improved supply chain performance. This paper suggests an answer through a simple standard performance measurement model. We will suggest that old systems of carrier competition could evolve to greater cooperation and coordination between business competitors, a state sometimes called "coopetition", by development of standard setting processes for sharing information while retaining specific service delivery structures to provide differentiated value to customers.
Keywords: 650; Ocean shipping; Alliances; Standardization; Supply chain integration; Ocean carrier differentiation